What Have We Learned about National Development Banks? Evidence from Brazil - Barboza, Ricardo (2023)
There are 553 development banks in the world: 18% of these institutions haveemerged since the 2008 financial crisis. There is a large theoretical literature on such institutions,but the evidence on their effectiveness is scattered. This paper provides a systematicreview of causal effect studies of one of the largest and most representative developmentbanks in the world, the Brazilian Development Bank (BNDES). We review 48 academic papersthat estimate BNDES loans and credit programs impact in several policy dimensions. Ingeneral, the evidence indicates that development banks can be an effective instrument to increaseinvestment, exports, employment and GDP, particularly when borrowers are micro,small and medium-sized companies. The Brazilian experience also suggests that developmentbanks can be an important tool to fight against climate change, reducing deforestation. Onthe other hand, evidence indicates that the greatest difficulty for these institutions is to generatepositive impacts on productivity, an essential variable for economic growth. Finally, theevidence is inconclusive on political influence on development bank’s loans. JEL Classification: H81; L38; L52.